Zastosowanie technologii mobilnych w marketingu - Łysik, Łukasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This article puts emphasis on changes that are already in progress in marketing and are bringingthis philosophy into a completely new stage, mobile marketing. The maim of this article is to showwhe-re and how mobile technology should be used to achieve best possible results in the marketingfield. The paper presents a few examples of usage of wireless tools and their application in Polish andfo-reign markets that reveals undiscovered yet potential of this technology. Besides, the authorpresents and defines the wide range of mobile tools and technologies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 339-349